1977
DOI: 10.1097/00000658-197701000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Influencing Survival

Abstract: Of patients with acute pancreatitis (AP), there remains a group who suffer life-threatening complications despite current modes of therapy. To identify factors which distinguish this group from the entire patient population, a retrospectiva analysis of 519 cases of AP occurring over a 5-year period was undertaken. Thirty-one per cent of these patients had a history of alcoholism and 47% had a history of biliary disease. The overall mortality was 12.9%. Of symptoms and signs recorded at the time of admission, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0
5

Year Published

1979
1979
1992
1992

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(67 citation statements)
references
References 18 publications
1
61
0
5
Order By: Relevance
“…Serious complications occur in 20 to 30% of the cases, with death in 8 to 20% , [4][5][6] This five-year retrospective study of all the admissions for AP to the University Hospitals in Riyadh (> 600 beds) shows that AP is not a common clinical entity in Saudi Arabia, forming a small proportion of the total number of annual hospital admissions. This finding should be representative of the incidence in major hospitals in the Kingdom, as the University Hospitals adopted an open-access policy during the study period and were accepting both Saudi nationals and expatriates with acute medical problems.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Serious complications occur in 20 to 30% of the cases, with death in 8 to 20% , [4][5][6] This five-year retrospective study of all the admissions for AP to the University Hospitals in Riyadh (> 600 beds) shows that AP is not a common clinical entity in Saudi Arabia, forming a small proportion of the total number of annual hospital admissions. This finding should be representative of the incidence in major hospitals in the Kingdom, as the University Hospitals adopted an open-access policy during the study period and were accepting both Saudi nationals and expatriates with acute medical problems.…”
Section: Discussionmentioning
confidence: 84%
“…The fourth patient had hyperlipidemia-associated acute relapsing pancreatitis and at recurrence had an amylase value of 1.23 μkat/L in grossly lipemic serum. According to the modified Glasgow scoring criteria, 22 (21%) of the 104 attacks of AP were severe, with a mean score of 4 out of a possible 8 (range, [3][4][5][6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As Jacobs et al 4) showed that the mortality rate was 71% without operation but was 36% with operation, the time of surgery is an important prognostic factor in this disease. Prompt decision must be made whether conservative therapy is sufficient, peritoneal perfusion should be decided, or surgical treatment is necessary.…”
Section: Discussionmentioning
confidence: 97%
“…AP is associated with serious complications in 20% to 30% of cases and death in 8% to 20%. This high rate of morbidity and mortality usually occurs among the "severe" form of the disease [6][7][8]. Apart from the early recognition of such "severe" cases using recently accepted Ranson and Imrie criteria and thus providing early identification and management of any serious complications, little progress has been achieved in improving the outcome of AP despite intensive worldwide research over the last several decades [9].…”
Section: Discussionmentioning
confidence: 99%